Record of extreme processes during the recession of the Warta ice sheet (Late Saalian) from the Sieradz Basin and adjacent moraine plateaus - Rdzany, Zbigniew; Frydrych, Małgorzata; Włodarski, Wojciech; Forysiak, Jacek (Acta Geographica Lodziensia, 2024)
The valley of the middle Warta River in the Sieradz Basin, as well as adjacent moraine upland plains, were subject to extreme glacial and glaciofluvial processes (glacial surges and glacial floods) during the recession of the Warta Glaciation (Late Saalian Glaciation). These processes had both local and regional extents. The article presents evidence of glaciotectonic processes and glacial floods. These processes were interconnected. Increased drainage of subglacial waters during glacial flooding influenced the mechanical coupling at the ice-substrate contact. As a result of this coupling, glaciotectonic deformations developed. Despite the undeniable evidence of high energy in both cases, enabling erosional processes and the transport of large quantities of meltwater and rock material, the morphological expression of these processes is moderate. Glacial surges resulted in the formation of push moraines with forms of small hills or merely shaping undulating uplands. On the other hand, glacial floods in the area covered by ice and in the foreland of the glacier were responsible for the creation of systems of deep erosional incisions. However, they are masked by younger sediments, mainly Vistulian and Holocene fluvial deposits.